Exploiting Modbus Protocol in Wired and Wireless Multilevel Communication Architecture - Guarese, Giuliano B. M.; Sieben, Felipe G.; Webber, Thais; Dillenburg, Marcos R.; Marcon, César (Anais do Simpósio Brasileiro de Engenharia de Sistemas Computacionais (SBESC); 2012: Anais do II Simpósio Brasileiro de Engenharia de Sistemas Computacionais, 2012)
This paper proposes an architectural improvement for the Modbus RTU protocol to integrate equipments in industrial automation networks, employing hybrid communication with wired Modbus RTU and wireless IEEE 802.15.4. These environments have different electromagnetic interferences, requiring protocols with noise immunity to varied equipments such as motors and generators. Modbus RTU is a simple and robust master-slave protocol that accepts the integration of a master with up to 247 slaves into a bus topology. In addition, the IEEE 802.15.4 protocol emerged recently as a wireless solution to industrial environments since it allows electromagnetic spectrum evaluation, and the choice of avoiding communications in noise frequencies and decreasing the error rate between packets. The proposed hybrid communication protocol increases control and topological limits imposed by Modbus RTU by enabling a wired/wireless tree-bus topology and master multiplexing. Moreover, the academy-industry cooperation resulted in features implemented in a gateway, whose efficiency is evaluated with practical experiments in different topologies.